AN ANALYSIS TYPES OF FIGURATIVE LANGUAGES FOUND IN LINKIN PARK “ONE MORE LIGHT ALBUM” SONGS LYRICS - I Made Yogi Aditya Wiguna; Desak Putu Eka Pratiwi; I Wayan Juniartha (IJELAL (International Journal of English Learning and Applied Linguistics), 2021)
This research aims to identify the kinds of figurative languages used in the chosen song lyrics of Linkin Park  and to examine the meanings of figurative languages in the song lyrics of Linkin Park. Several song lyrics from Linkin Park that were randomly taken are the data base of this analysis. In the analysis of data from this report, descriptive and qualitative methods were used. The theory of Knickerbocker and Reninger (1963: 367) studied the types of figurative languages and also the accepted theory of meaning proposed by Leech (1981: 16) will be analyzed in the selected song lyrics of Linkin Park to explain the meaning of figurative language. The researcher assumes, after the study has been finished, that the chosen song lyrics of Linkin Park consist of of 21 lyrics that used figurative language. The sentence has figurative language in Linkin Park song lyrics are 14% of simile, 9% of metaphor, 19% of personification, 48% of hyperbole, 5% of synecdoche, 5% of metonymy.